SLANG LANGUAGE IN THE NOVEL ANALOGY CINTA BERDUA BY DARA PRAYOGA - Supyan Sori; Agus Sulaeman; Enawar Enawar; Ahmad Amarullah (STIBA IEC JAKARTA, 2021)
The purpose of this study is to describe the slang contained in Novel literature ‘’Analogi Cinta Berdua” by Dara Prayoga’’ Language is a tool used by humans to communicate language in the form of sound symbols issued by human speech organs, Slang is contemporary or easy to disappear and is not permanent, therefore it is rare to find slang that is permanent and long used for a long period of time. The approach used is qualitative to analyze the novel using the content analysis method From the results of the study, it was found that the use of slang in the form of linguistic symbols such as. Yoi, sekarang gue punya pacar!” From these quotations, researchers can find out the use of slang. The quote is translated into Indonesian as